2011
DOI: 10.1007/s10555-011-9312-1
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 and Gastric Cancer

Abstract: Gastric cancer remains a leading cause of cancer-related deaths worldwide, although its incidence has been steadily declining during recent decades. Expression of cyclooxygenase-2 (COX-2) is elevated in gastric carcinomas and in their precursor lesions. COX-2 expression associates with reduced survival in gastric cancer patients, and it has also been shown to be an independent factor of poor prognosis. Several molecular mechanisms are involved in the regulation of COX-2 expression in gastric cancer cell lines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 89 publications
1
42
0
1
Order By: Relevance
“…This results in the enhanced synthesis of prostaglandins in neoplastic and inflamed tissues (Coussens and Werb, 2002). Overexpression of COX-2 has been demonstrated in several adult epithelial tumors such as colon cancer (Lai et al, 2004), gastric cancer (Thiel et al, 2011) and hepatocellular carcinoma (Ogunwobi and Liu, 2011). COX-2 is linked to tumor-promoting effects, including tumor growth and metastasis, by stimulating invasiveness and angiogenesis (Chen et al, 2009;Liu et al, 2011), inhibiting apoptosis and immune surveillance (Ohno et al, 2005), and enhancing drug resistance (Mehar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This results in the enhanced synthesis of prostaglandins in neoplastic and inflamed tissues (Coussens and Werb, 2002). Overexpression of COX-2 has been demonstrated in several adult epithelial tumors such as colon cancer (Lai et al, 2004), gastric cancer (Thiel et al, 2011) and hepatocellular carcinoma (Ogunwobi and Liu, 2011). COX-2 is linked to tumor-promoting effects, including tumor growth and metastasis, by stimulating invasiveness and angiogenesis (Chen et al, 2009;Liu et al, 2011), inhibiting apoptosis and immune surveillance (Ohno et al, 2005), and enhancing drug resistance (Mehar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that increased COX-2 expression is an independent prognostic factor for poor prognosis and is associated with reduced survival in patients with GC (19). Therefore, increasing attention had been directed to the mechanisms of celecoxib action on GC.…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 has been shown to be involved in the processes of inflammation and carcinogenesis [56], and previous studies indicate that COX-2 expression is associated with H. pylori-induced gastritis and stomach carcinogenesis in humans [57,58]. H. pylori infection and excessive salt intake synergistically enhance COX-2 and iNOS expression in the gastric mucosa of gerbils [59].…”
Section: Cox-2 Inhibitorsmentioning
confidence: 99%